KONSTRUKSI KURIKULUM PESANTREN IBNUL AMIN MENURUT PEMIKIRAN MAHFUZ AMIN - Rahmadi . (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2010)
This paper tries to explore the basic principality of Mahfuz Amin thought in constructing the curriculum of Ibnul Amin Pesantren, analyzed through the curriculum developing concept, namely: (1) the basic of the curriculum (religion, philosophy, sociology, and philosophy); (2) the principle of the curriculum; and (3) the orientation of the curriculum. The curriculum product from the thought of Mahfuz Amin is the curriculum that have the orientation to tafaqquh fi al-dn and takhasshus dn conservationally and traditionally with the goal to make life the religion knowledge based on ahlus sunnah wal jamaah value.